Push-out Bond Strength of Calcium Enriched Mixture Exposed to Alkaline Environment - Sobhnamayan F; Adl A; Sarbaz M; Sadat Shojaee N; Ghoraishi Abhari MS (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Calcium hydroxide which is commonly used as an intracanal medicament, changes the pH of dentin and periradicular tissues to an alkaline pH. In some clinical situations, endodontic reparative cements like calcium enriched mixture cement are used after calcium hydroxide therapy. However, the alkaline pH may affect the physical properties of this cement. Objectives: This study was designed to evaluate the effect of alkaline pH on the push-out bond strength of calcium enriched mixture. Materials and Methods: 80 root slices were prepared from single-rooted human teeth and their lumens were instrumented to achieve a diameter of 1.3mm. Calcium enriched mixture (CEM) was mixed according to the manufacturer's instruction and introduced into the lumens of root slices. The specimens were then randomly divided into 4 groups (n = 20) and wrapped in pieces of gauze soaked in synthetic tissue fluid (STF) buffered in potassium hydroxide at pH values of 7.4, 8.4, 9.4, or 10.4. The samples were incubated for 4 days at 37°C. The push-out bond strengths were then measured using a universal testing machine. Failure modes were examined under a light microscope at ×20 magnification. The data were analyzed using one-way analysis of variance and Tukey's post hoc tests. Results: The greatest (1.41 ± 0.193 MPa) and lowest (0.8 ± 0.06 MPa) mean push-out bond strengths were observed after exposure to pH values of 7.4 and 8.4, respectively. There were significant differences between the neutral group and the groups with pH of 8.4 (p = 0.008) and 10.4 (p = 0.022). The bond failure was predominantly of cohesive type for all experimental groups. Conclusions: Under the condition of this study, alkaline pH adversely affected the Push-out bond strength of CEM cement.